Impact of Entrepreneurial Orientation and Innovation Strategy on MSME Performance in Bali's Apparel Sector - Hifzhan Thousani; Mochammad Heri Edy (Universitas Muhammadiyah Palu, 2024)
This study aims to explore the influence of entrepreneurial orientation on the performance of micro, small, and medium enterprise in the apparel industry in Bali, with innovation strategy as an intervening variable and technological resources as a moderating variable. Using the Resource-Based View (RBV) and Contingency Theory approaches, this study involved 220 randomly selected participants. Data analysis was performed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results show that entrepreneurial orientation has a significant positive impact on business performance through innovation strategy. Additionally, technological resources strengthen the relationship between entrepreneurial orientation and business performance. These findings highlight the importance of entrepreneurial orientation, innovation strategy, and technological support in enhancing MSME performance in the apparel sector. This research contributes to the literature by providing insights into how the combination of entrepreneurial orientation and technology can be optimized to achieve competitive advantage in the context of micro, small, and medium enterprise in Bali.